ANALISIS PERBANDINGAN PERANAN JALUR SUKU BUNGA DAN JALUR NILAI TUKAR PADA MEKANISME TRANSMISI KEBIJAKAN MONETER DI ASEAN : STUDI KOMPARATIF (INDONESIA, MALAYSIA, SINGAPURA) - Rayati Togatorop; Wahyu Ario Pratomo (Ekonomi dan Keuangan, 2014)
The purpose of this research to knowing how the role channels of interest rate and exchange rate channels of monetary policy transmission mechanism of ASEAN (Study comparative : Indonesia, Malaysia, Singapore). The variable of this research are deposit interest rate, lending interest rate, rill interest rate, exchange rate, net export, inflation and GDP. Analysis tools used in this research is Vector Auto Regression (VAR) model, that is Variance Decomposition and Impulse Response Function (IRF). This research used data start from 2000 until 2012. The results of this research the role of interest rate channels and exchange rate channels of monetary policy transmission mechanism is effective in Indonesia and Malaysia. That base from variance decomposition results test and impulse response function results. While in Singapore exchange rate channels of monetary policy transmission mechanism is effective to response the economy growth.Key word: Interest Rate Channel, Exchange Rate Channel, Monetary Policy Transmission Mechanism, Indonesia, Malaysia,singapore